PENGARUH KARAKTERISTIK PERUSAHAAN DAN KARAKTERISTIK AUDITOR TERHADAP AUDIT REPORT LAG Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di Bursa Efek Indonesia pada periode Sebelum Pandemi (2017-2018) dan periode Saat Pandemi (2019-2020) - Tiara Putri Pertiwi; Paulus Th. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2022)
This study aims to examine the factors that affect Audit Report Lag (ARL). The factors used in this study are selected by looking at the characteristics of the company and the characteristics of an auditor. The independent variables used in this study are company characteristics as proxied by profitability, financial distress, leverage, company size, and company age, whereas auditor characteristics as proxied by auditor reputation, auditor’s industry specialization, audit tenure and audit opinion.Responding to the Covid-19 pandemic, the Financial Services Authority (OJK) has established regulations regarding the maximum time restriction for delivering audited financial reports valid for 2019 and 2020, which was previously set at March 30 to May 31. Therefore, this study employs two research periodes: before the pandemic (2017-2018) and during the pandemic (2019-2020). The sample is determined using the purposive sampling approach and numerous criteria. The total sample obtained was 351 companies in before the pandemic (2017-2018) and 407 companies during the pandemic (2019-2020). The analytical method used for this study is multiple linear regression analysis using Partial Least Squares (PLS) with SmartPLS software. Hypothesis testing was done by statistical t-test.The results showed that in the period before the pandemic (2017-2018) profitability, financial distress, company size, and audit tenure did not show significant influence but has a negative effect on audit report lag and leverage, company age, and auditor reputation had a positive effect but did not show significant influence on audit report lag. However, there is a significant negative effect of auditor’s industry specialization and audit opinion on audit report lag. Whereas, during the pandemic (2019-2020) profitability, leverage, company size, and auditor’s industry specialization did not show significant influence but has a negative effect on audit report lag and financial distress, company age, and audit tenure had a positive effect but did not show significant influence on audit report lag. However, there is a significant negative effect of auditor reputation and audit opinion on audit report lag.